2019
DOI: 10.1038/s41598-019-54535-x
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Effects on Inflammatory Biomarkers and Lipid Profiles among Diabetic and Cardiovascular Disease Patients: A Systematic Review and Meta-Analysis

Abstract: The purpose of this systematic review and meta-analysis was to investigate omega-3 fatty acids’ influence on 12 inflammatory biomarkers—LDL, HDL, total cholesterol, TG, HbA1c, Apo AI, Apo AII, Apo B, CRP, TNF-α, glucose, and fasting blood glucose among diabetic and cardiovascular disease (CVD) patients. We searched articles in six database engines, and 16 of the 696 articles reviewed met the inclusion criteria. Among these, lipid and inflammatory biomarkers investigated commonly included total cholesterol (11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 76 publications
2
50
1
4
Order By: Relevance
“…ARA, an omega-6 fatty acid, and EPA and DHA, omega-3 fatty acids, affect inflammatory and immune responses. In general, eicosanoids derived from EPA and DHA are less inflammatory than those derived from ARA [32]. For example, eicosanoid receptors typically have a lower affinity for the EPA-derived mediator than for the ARA-derived one [10,[33][34][35].…”
Section: Fatty Acids and Inflammationmentioning
confidence: 99%
“…ARA, an omega-6 fatty acid, and EPA and DHA, omega-3 fatty acids, affect inflammatory and immune responses. In general, eicosanoids derived from EPA and DHA are less inflammatory than those derived from ARA [32]. For example, eicosanoid receptors typically have a lower affinity for the EPA-derived mediator than for the ARA-derived one [10,[33][34][35].…”
Section: Fatty Acids and Inflammationmentioning
confidence: 99%
“…Clinical studies and a recent meta-analysis, including 20 clinical trials, have c o n fi r m e d t h e r a p e u t i c e ff e c t s o f n -3 L C -P U F A supplementation in rheumatoid arthritis patients (Gioxari et al, 2018;Woodman et al, 2019). Moreover, a systematic review and meta-analysis by Natto et al (2019) concluded that these omega-3 fatty acids may be associated with lower plasma levels of inflammatory biomarkers in diabetic patients. However, results regarding their effect on glucose metabolism, insulin resistance, and type 2 diabetes are less clear (Stella et al, 2018).…”
Section: The Main Components Of the Oil From Cf And Their Effect On Imentioning
confidence: 99%
“… 99 A recent meta-analysis of 13 randomized controlled trials, which included over 120,000 participants, confirmed that PUFA supplementation reduces the risk for CHD and CVD, myocardial infarction, and death due to CHD and CVD. 100 101 A systematic review and meta-analysis by Natto et al 102 also concluded that PUFA consumption may be associated with lower plasma levels of inflammatory biomarkers in patients with diabetes. However, results regarding the effects of PUFAs on glucose metabolism, insulin resistance, and type 2 diabetes are less clear, 103 most likely due to differences in the choice of PUFA preparation, dosage, and intervention.…”
Section: Treatment Strategiesmentioning
confidence: 99%